Evolusi Konsep Sunnah dalam Lintasan Sejarah - rohman, Taufikur (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2013)
A conversation about the sunnah is a long and ongoing discussion to the present. The central issue that continues is about the nature, status, and authority of the sunnah. This issue becomes so important because the position of the Prophet Muhammad as the messenger of Allah, so that his words and actions received by most Muslims as a source of religious authority and the second law after the Koran. Actually, the concept of the sunnah has evolved from time-to time. At the time of the Prophet Muhammad, sunnah is understood in an ideal form of behavior exemplified by the Prophet Muhammad who was always getting guidance from God throughout his life. At the time of the companions, this concept has been sustained and even further developed with the ijtihÃ¢d of the Companions, especially al-KhulafÃ¢â al-RÃ¢shidÃ»n that applied to society at that time. Discussing about sunnah, than, can not avoid discussions about hadith, because hadÃ®thes are vehicles of the sunnah. At glance, the term sunnah and hadÃ®th has same meaning, that is the tradition of the Prophetic tradition. This paper tries to highlight the development of the concept of the sunnah from the Prophet until the era of al-ShÃ¢fiâÃ®.